Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Reconstruction of 3D Surfels from Neural Radiance Fields - Telaprolu, Vipasyan

Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

Zusammenarbeit von Frühförderung und Kita im Förderschwerpunkt Sehen - Jesuthasan, Jonitta

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Assessment of long-term dietary cadmium exposure in children in Germany: Does consideration of data from total diet studies reduce uncertainties from food monitoring programmes? - Kolbaum, AE; Jung, C; Jaeger, A; Libuda, Lars; Lindtner, O (Food Chem Toxicol)

Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen - Spiller, Achim; Nieberg, Hiltrud; Renner, Britta; Balmann, Alfons; Birna, Regina; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kai-Uwe; Linseisen, Jakob; Nöthlings, Ute; et al.
Zitieren als: Wissenschaftlicher Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucher- schutz beim BMEL (2023): Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen. Gutachten. Berlin.

Numerical analysis of failure modeling in clinching process chain simulation - Bielak, Christian Roman; Böhnke, Max; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. The application of the mechanical joining process clinching allows the assembly of different sheet metal materials with a wide range of material thickness configurations, which is of interest for lightweight multi-material structures. In order to be able to predict the clinched joint properties as a function of the individual manufacturing steps, current studies focus on numerical modeling of the entire clinching process chain. It is essential to be able to take into account the influence of the joining process-induced damage on the load-bearing capacity of the joint during the loading phase. This study presents a numerical damage accumulation in the clinching process based on an implemented Hosford-Coulomb failure model using a 3D clinching process model applied on the aluminum alloy EN AW-6014 in temper T4. A correspondence of the experimentally determined failure location with the element of the highest numerically determined damage accumulation is shown. Moreover, the experimentally determined failure behavior is predicted to be in agreement in the numerical loading simulation with transferred pre-damage from the process simulation.

proDruck 3D-Druck – Technologie der Industrie 4.0 – als Mittel der Inklusion für Menschen mit Behinderungen in die Arbeitswelt - Kruse, Anne; Müller, Laura; Ott, Manuel; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

3D-Druck – Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Müller, Laura; Ott, Manuel; Jung, Philipp; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

Deriving 3D Functional Brain Regions from Multi-Slice Functional Ultrasound Data Using ICA and IVA - Lehmann, Isabell; Adali, Tülay; Kruizinga, Pieter; Hunyadi, Borbála (2023 57th Asilomar Conference on Signals, Systems, and Computers)

A 28-Gb/s 27.2mW NRZ Full-Rate Bang-Bang Clock and Data Recovery in 22 nm FD-SOI CMOS Technology - Iftekhar, Mohammed; Gowda, Harshan; Kneuper, Pascal; Sadiye, Babak; Müller, Wolfgang; Scheytt, Christoph (2023 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

Treuwidrige Darlehenskündigung durch Bank nach Herbeiführung der Zahlungsunfähigkeit des Darlehensnehmers durch eigenmächtige Aufteilung eines eingegangenen Betrags auf verschiedene Verbindlichkeiten. Anmerkung zu LG Aachen, Urt. v. 20.12.2022 - 10 O 137/22 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Methodenentwicklung zur Versagensanalyse aufgrund der Aushärtung vorgeschädigter Klebverbindungen in stahlintensiven Mischbaustrukturen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Carillo Beber, Vinicius; Nagel, Christof; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Weiterentwicklung der induktiven Schnellhärtung von Klebverbindungen für robuste Fertigungsprozesse unter Berücksichtigung von serienrelevanten Einflussfaktoren - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (22. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analyse des Versagensverhaltens geklebter Stahl-Verbindungen beim werkstoffschonenden Entfügen in der Karosserieinstandsetzung - Chudalla, Nick; Meschut, Gerson; Bartley, Aurélie; Wibbeke, Tim Michael (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Striewe, Marius; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Steinmann, Paul (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Compensation of LF Common-Mode Noise by the internal DC/DC-Stage for transformerless On-Board Chargers at Three- and Single-Phase Operation - Schafmeister, Frank (International Conference on Electric & Electronic in Hybrid and Electric Vehicles and Electric Energy Management (EEHE),)

An Open-Source Transistor Database and Toolbox as an Unified Software Engineering Tool for Managing and Evaluating Power Transistors - Förster, Nikolas; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (Proc. 37th IEEE Applied Power Electronics Conference (APEC))

Robust Hysteresis Control for LLC Resonant Converters Using a Fully Isolated Measurement Scheme - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Systematisierung einer rechnergestützten Auswertemethode zur Versagensanalyse geklebter Verbindungen - Chudalla, Nick; Teutenberg, Dominik; Meschut, Gerson; Schneider, Miriam; Smart, Dominik (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Dataset for random uniform distributions of 2D circles and 3D spheres. - Wojciechowski, M (Data Brief)

Increased Cognitive Demands Affect Agility Performance in Female Athletes - Implications for Testing and Training of Agility in Team Ball Sports - Büchel, Daniel; Gokeler, Alli; Heuvelmans, Pieter; Baumeister, Jochen (Perceptual and Motor Skills)
Agility, a key component of team ball sports, describes an athlete´s ability to move fast in response to changing environments. While agility requires basic cognitive functions like processing speed, it also requires more complex cognitive processes like working memory and inhibition. Yet, most agility tests restrict an assessment of cognitive processes to simple reactive times that lack ecological validity. Our aim in this study was to assess agility performance by means of total time on two agility tests with matched motor demands but with both low and high cognitive demands. We tested 22 female team athletes on SpeedCourt, using a simple agility test (SAT) that measured only processing speed and a complex agility test (CAT) that required working memory and inhibition. We found excellent to good reliability for both our SAT (ICC = .79) and CAT (ICC =.70). Lower agility performance on the CAT was associated with increased agility total time and split times ( p < .05). These results demonstrated that agility performance depends on the complexity of cognitive demands. There may be interference-effects between motor and cognitive performances, reducing speed when environmental information becomes more complex. Future studies should consider agility training models that implement complex cognitive stimuli to challenge athletes according to competitive demands. This will also allow scientists and practitioners to tailor tests to talent identification, performance development and injury rehabilitation.
Keywords: Sensory Systems; Experimental and Cognitive Psychology

ADAGIO - Automated Data Augmentation of Knowledge Graphs Using Multi-expression Learning - Dreßler, Kevin; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 33rd ACM Conference on Hypertext and Hypermedia)
The creation of an RDF knowledge graph for a particular application commonly involves a pipeline of tools that transform a set ofinput data sources into an RDF knowledge graph in a process called dataset augmentation. The components of such augmentation pipelines often require extensive configuration to lead to satisfactory results. Thus, non-experts are often unable to use them. Wepresent an efficient supervised algorithm based on genetic programming for learning knowledge graph augmentation pipelines of arbitrary length. Our approach uses multi-expression learning to learn augmentation pipelines able to achieve a high F-measure on the training data. Our evaluation suggests that our approach can efficiently learn a larger class of RDF dataset augmentation tasks than the state of the art while using only a single training example. Even on the most complex augmentation problem we posed, our approach consistently achieves an average F1-measure of 99% in under 500 iterations with an average runtime of 16 seconds
Keywords: 2022 RAKI SFB901 deer dice kevin knowgraphs limes ngonga sherif simba

XCS on Embedded Systems: An Analysis of Execution Profiles and Accelerated Classifier Deletion - Hansmeier, Tim; Brede, Mathis; Platzner, Marco (GECCO '22: Proceedings of the Genetic and Evolutionary Computation Conference Companion)

Methodenentwicklung zur Verbesserung der Schädigungsmodellierung in der numerischen 3D-Belastungssimulation mechanischer Fügeverfahren unter Berücksichtigung der fügeinduzierten Vorbeanspruchung - Otroshi, Mortaza; Meschut, Gerson

Methodenentwicklung zur rechnerischen Auslegung geklebter Stahlverbindungen unter Alterungsbeanspruchung im Stahl- und Anlagenbau - Sander, Sascha; Teutenberg, Dominik; Meschut, Gerson; Kötz, Fabian; Matzenmiller, Anton; Kasper, Yann; Ummenhofer, Thomas (22. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European Journal of Nutrition)
Abstract Purpose The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Brief Announcement: The (Limited) Power of Multiple Identities: Asynchronous Byzantine Reliable Broadcast with Improved Resilience through Collusion - Götte, Thorsten; Scheideler, Christian (SPAA ’22: 34th ACM Symposium on Parallelism in Algorithms and Architectures, Philadelphia, PA, USA, July 11 - 14, 2022)

Decision Support Ecosystems: Deﬁnition and Platform Architecture - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Decision Support Systems XII: Decision Support Addressing Modern Industry, Business, and Societal Needs)
Decision support systems are crucial in helping decision makers to quickly identify optimal business decisions in increasingly volatile and complex business environments. However, the ideal DSS for one decision maker may not optimally address the requirements for decision support of another decision maker. This is due to differences between decision makers in business goals, regulatory restrictions or availability of resources such as data. By using a suboptimal DSS, decision makers risk implementing suboptimal decision recommendations which endanger the success of their business. This presents DSS developers with the challenge to implement a customizable DSS which can be tailored to the individual requirements for decision support of a single decision maker. In order to address this challenge, we suggest a decision support ecosystem in which DSS developers, decision makers and other domain experts collaborate using a shared platform to provide and combine reusable decision support services into a tailored DSS. The contribution of our paper is twofold: First, we define the concept of a decision support ecosystem with respect to existing digital business ecosystems and discuss expected benefits and challenges. Second, we present a reference architecture for a shared platform supporting the realization of a decision support ecosystem. We demonstrate our contributions in the example application domain of regional energy distribution network planning.

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))
In this work, methods will be evaluated to numerically calculate the passive electrical parameters of planar coils. These parameters can then be used to optimize inductive applications such as wireless power transmission. The focus here will be on inductive localization, which uses high-frequency magnetic fields and the resulting induced voltage to provide localization through the coupling parameter mutual inductance. To achieve localization with high accuracy and best possible operation (resonance, signal strength, etc.), the coil parameters need to be well known. For this reason, some numerical methods for the calculation of these quantities are presented and validated. In addition, the physical effects are thereby considered in more detail, allowing the localization procedure to be better optimized compared to simulative black-box methods. The goal should be a dedicated simulation platform for planar coils to be able to develop training data for neural networks and to test and optimize localization algorithms.
Keywords: Simulation Environment; Inductive Localization; Coil Parameters; Inductive Applications; Near-Field

Collaborative Modeling of Use Case & Damage Scenarios in Online Workshops Using a 3D Environment - Japs, Sergej; Schmidt, Sebastian; Kargl, Frank; Kaiser, Lydia; Kharatyan, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of technical systems requires close cooperation of stakeholders from different disciplines. This collaboration takes place in workshops. Driven by digitalization and by the current pandemic such workshops take place primarily online. Suitable collaboration tools and methods are crucial to success. At the beginning of such workshops, use and damage scenarios are identified. In this paper, we presented a method and tool for identifying and modeling use and damage scenarios, which we evaluated in 14 online workshops with a total of 118 participants over a period of almost 3 years.

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, C. R.; Böhnke, M.; Bobbert, M.; Meschut, G. (The Minerals, Metals & Materials Series)

2022 Edsger W. Dijkstra Prize in Distributed Computing - Aguiliera, Marcos; Richa, Andréa W.; Schwarzmann, Alexander A.; Panconesi, Alessandro; Scheideler, Christian; Woelfel, Philipp (PODC ’22: ACM Symposium on Principles of Distributed Computing, Salerno, Italy, July 25 - 29, 2022)

A Data Driven Modelling Approach for the Strain Rate Dependent 3D Shear Deformation and Failure of Thermoplastic Fibre Reinforced Composites: Experimental Characterisation and Deriving Modelling Parameters - Gerritzen, Johannes; Hornig, Andreas; Gröger, Benjamin; Gude, Maik (Journal of Composites Science)
The 3D shear deformation and failure behaviour of a glass fibre reinforced polypropylene in a shear strain rate range of γ˙=2.2×10−4 to 3.4 1s is investigated. An Iosipescu testing setup on a servo-hydraulic high speed testing unit is used to experimentally characterise the in-plane and out-of-plane behaviour utilising three specimen configurations (12-, 13- and 31-direction). The experimental procedure as well as the testing results are presented and discussed. The measured shear stress–shear strain relations indicate a highly nonlinear behaviour and a distinct rate dependency. Two methods are investigated to derive according material characteristics: a classical engineering approach based on moduli and strengths and a data driven approach based on the curve progression. In all cases a Johnson–Cook based formulation is used to describe rate dependency. The analysis methodologies as well as the derived model parameters are described and discussed in detail. It is shown that a phenomenologically enhanced regression can be used to obtain material characteristics for a generalising constitutive model based on the data driven approach.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Dimensionierung und Optimierung von im FDM-Verfahren 3D-gedruckten Direktverschraubungen aus ABS - Moritzer, Elmar; Held, Christian; Hillemeyer, Johannes (Joining Plastic)

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Can Machine Translation be a Reasonable Alternative for Multilingual Question Answering Systems over Knowledge Graphs? - Perevalov, Aleksandr; Both, Andreas; Diefenbach, Dennis; Ngonga Ngomo, Axel-Cyrille (WWW ’22: The ACM Web Conference 2022, Virtual Event, Lyon, France, April 25 - 29, 2022)

Kronecker Decomposition for Knowledge Graph Embeddings - Demir, Caglar; Lienen, Julian; Ngonga Ngomo, Axel-Cyrille (HT ’22: 33rd ACM Conference on Hypertext and Social Media, Barcelona, Spain, 28 June 2022- 1 July 2022)

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

On non-extinction in a Fleming-Viot-type particle model with Bessel drift - Kolb, Martin; Liesenfeld, Matthias (Electronic Journal of Probability)
Motivated by the work [6] of Mariusz Bieniek, Krzysztof Burdzy and Soumik Pal we study a Fleming-Viot-type particle system consisting of independently moving particles each driven by generalized Bessel processes on the positive real line. Upon hitting the boundary {0} this particle is killed and an uniformly chosen different one branches into two particles. Using the symmetry of the model and the self similarity property of Bessel processes, we obtain a criterion to decide whether the particles converge to the origin at a finite time. This addresses open problem 1.4 in [6]. Specifically, inspired by [6, Open Problem 1.5], we investigate the case of three moving particles and refine the general result of [6, Theorem 1.1(ii)] extending the regime of drift parameters, where convergence does not occur – even to values, where it does occur when considering the case of only two particles.

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara